2010
DOI: 10.1007/s00415-010-5558-8
|View full text |Cite
|
Sign up to set email alerts
|

Pneumonia and in-hospital mortality in the context of neurogenic oropharyngeal dysphagia (NOD) in stroke and a new NOD step-wise concept

Abstract: The aim of our work was to develop a step-wise concept for investigating neurogenic oropharyngeal dysphagia (NOD) that could be used by both trained nursing staff as well as swallowing therapists and physicians to identify patients with NOD at an early stage and so enable an appropriate therapy to be started. To achieve this objective, we assessed uniform terminology and standard operating procedures (SOP) in a new NOD step-wise concept. In-house stroke mortality rates and rates of pneumonia were measured over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
13

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(51 citation statements)
references
References 26 publications
2
36
0
13
Order By: Relevance
“…does not classify dysphagia as a change in oral and/ or pharyngeal phase, unlike other tools concerned with data on the speech organs and swallowing biomechanics 9,[11][12][13][14][15][16] . This is because the dysphagia study in post-stroke patients in the acute phase should mainly focus the evaluation of the risk of bronchial aspiration and subsequent definition of a safer and more effective oral feeding 1,[3][4][5]9,27 . In this study, the GUSS scale allowed not only the identification of dysphagia, but also the classification of its severity and clinical changes of the acute phase of stroke.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…does not classify dysphagia as a change in oral and/ or pharyngeal phase, unlike other tools concerned with data on the speech organs and swallowing biomechanics 9,[11][12][13][14][15][16] . This is because the dysphagia study in post-stroke patients in the acute phase should mainly focus the evaluation of the risk of bronchial aspiration and subsequent definition of a safer and more effective oral feeding 1,[3][4][5]9,27 . In this study, the GUSS scale allowed not only the identification of dysphagia, but also the classification of its severity and clinical changes of the acute phase of stroke.…”
Section: Discussionmentioning
confidence: 99%
“…Dysphagia is clinically diagnosed in 40 to 70% of patients in the first three days after stroke, and the incidence of aspiration of saliva, food and/or liquid ranges from 20 to 45% in the first five days [1][2][3] . Dysphagia is associated with impaired food intake, which can lead to malnutrition during hospital stay and to pulmonary complications, especially pneumonia by aspiration [3][4][5][6][7] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…La valoración modificada de la deglución (MSA) ayuda al personal que la realiza a identificar a los pacientes con disfagia y a derivarlos a los correspondientes especialistas en disfagia para su posterior valoración (18). Se pueden identificar limitaciones deglutorias graves en las dos primeras partes de la valoración.…”
Section: Evaluación De La Disfagia En El Paciente Con Ictusunclassified
“…On the other hand, it is reported that oral cleaning and functional support from the early phase in the acute stages is effective in avoiding secondary infectious diseases. 10,11) Based on these fi ndings, studies have examined the activities and efforts by dentists and dental hygienists in the arena of professional oral health care in the acute or emergency stage. 12 14) On the other hand, these reports indicated that how the oral health status of patients was an indicator of the diffi culties faced when aiming to improve the oral health with regard to general health issues and exacerbation of diseases.…”
Section: Survey On the Issues And The Changes Of Oral Health Conditiomentioning
confidence: 99%